Synthesis, preparation and characterization of UV-cured methacrylated polysulfone-based membranes. (December 2015) - Sangermano, M.; Farrukh, M.Mian; Tiraferri, A.; Dizman, C.; Yagci, Y.
Graphical abstract: Abstract: A new two-step method involving non-solvent induced phase separation (NIPS) and a UV curing process for the preparation of networked-polysulfone membranes is described. In this approach, first, methacrylated polysulfone macromonomers (PSU-DM)s were prepared by polycondensation followed by end-group esterification. PSU-DMs thin films containing phenylbis(2, 4, 6-trimethylbenzoyl)phosphine oxide (BAPO) photoinitiator cast on glass plates were successively subjected to NIPS and UV curing processes to produce the ultrafiltration membranes. The reverse sequence, i.e. first UV-curing followed by NIPS was also applied. Although different double bond conversions were attained, both procedures essentially yielded structurally analogous membranes which were insoluble in DMF, DMSO, and boiling water. UV-curing behavior, structure, thermo-mechanical and morphological properties of the membranes were investigated. Regardless of the preparation sequences, membranes exhibited pure water permeability in the range of tight ultrafiltration membranes.